Mean Platelet Volume as an Indicator of Glycemic Control in Type 2 Diabetes Mellitus (Medical Forum Monthly, 2024)
Objective: To study platelet counts (PC), mean platelet volume (MPV) and glycated HbA1 in type 2 Diabetes mellitus (T2DM).Study Design: Case control studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Indus Medical College Hospital, Tando Muhammad Khan, Sindh from March to November 2015Materials and Methods: A sample of 150 subjects; comprising of Group A- controls (n=50), Group B- controlled diabetics (n=50) and Group C- (n=50) uncontrolled diabetics. DM was diagnosed according to American Diabetes Association. Permission was taken from ethics review committee of institute. Only willing subjects were included after they signed consent proforma voluntarily. Blood pressure, BMI, Blood glucose, Platelet counts, MPV and HbA1c were determined Data was typed on Microsoft excel, and then pasted SPSS 22.0 sheet for statistical analysis. Chi square test, one way ANOV, post-Hoc Tukey Cramer and Pearson`s association was used for analysis of data variables. All data was analyzed at Confidence interval of 95% (≤0.05)Results: MPV was raised in Diabetics in particular with uncontrolled glycemic index as shown in table II. MPV showed negative correlation with platelets was found with MPV (r = -0.27, p=0.03). MPV was positively correlated with glycated HbA1 (r = 0.78, p= 0.0001). HbA1c as high as 14.3% was noted in uncontrolled diabetics.Conclusion: The present study reports raised Mean platelet volume in Diabetics in particular uncontrolled diabetics. MPV showed positive correlation with HbA1c and negative correlation with platelet count.